Stem cell generation and choice of fate: role of cytokines and cellular microenvironment - Constantinescu, S.N. (J Cell Mol Med, 2007)
Hematopoietic stem cells (HSC) have provided a model for the isolation, enrichment and transplantation of stem cells. Gene targeting studies in mice have shown that expression of the thrombopoietin receptor (TpoR) is linked to the accumulation of HSCs capable to generate long‐term blood repopulation when injected into irradiated mice. The powerful increase in vivo in HSC numbers by retrovirally transduced HOX4B, a homeotic gene, along with the role of the TpoR, suggested that stem cell fate, renewal, differentiation and number can be controlled. The discovery of the precise region of the mouse embryo where HSCs originate and the isolation of supporting stromal cell lines open the possibility of identifying the precise signals required for HSC choice of fate. The completion of human genome sequencing coupled with advances in gene expression profiling using DNA microarrays will enable the identification of key genes deciding the fate of stem cells. Downstream from HSCs, multipotent hematopoietic progenitor cells appear to co‐express a multiplicity of genes characteristic of different blood lineages. Genomic approaches will permit the identification of the select group of genes consolidated by the commitment of these multipotent progenitors towards one or the other of the blood lineages. Studies with neural stem cells pointed to the unexpected plastic nature of these cells. Isolation of stem cells from multiple tissues may suggest that, providing the appropriate environment/signal, tissues could be regenerated in the laboratory and used for transplantation. A spectacular example of influence of the environment on cell fate was revealed decades ago by using mouse embryonic stem cells (ES). Injected into blastocysts, ES cells contribute to the formation of all adult tissues. Injected into adult mice, ES cells become cancer cells. After multiple passages as ascites, when injected back into the blastocyst environment, ES‐ derived cancer cells behaved again as ES cells. More recently, the successful cloning of mammals and reprogramming of transferred nuclei by factors in the cytoplasm of oocytes turned back the clock by showing that differentiated nuclei can be “re‐booted” to generate again the stem cells for different tissues.